Post-transcriptional regulation of rat carnitine octanoyltransferase. (May 2001) - Hegardt, F. G.; Bach, M.; Asins, G.; Caudevilla, C.; Morillas, M.; Codony, C.; Serra, D.
Abstract : Carnitine octanoyltransferase (COT) produces three different transcripts in rat through cis - and trans -splicing reactions, which can lead to the synthesis of two proteins. The occurrence of the three COT transcripts in rat has been found in all tissues examined and does not depend on sex, fat feeding, peroxisome proliferators or hyperinsulinaemia. Rat COT exon 2 contains a putative exonic splicing enhancer (ESE) sequence. Mutation of this ESE (GAAGAAG) to AAAAAAA decreased trans -splicing in vitro, from which it is deduced that this ESE sequence is partly responsible for the formation of the three transcripts. The protein encoded by cis -spliced mRNA of rat COT is inhibited by malonyl-CoA and etomoxir. cDNA species encoding full-length wild-type COT and one double mutant COT were expressed in Saccharomyces cerevisiae . The recombinant enzymes showed full activity towards both substrates, carnitine and decanoyl-CoA. The activity of the doubly mutated H131A/H340A enzyme was similar to that of the rat peroxisomal enzyme but was completely insensitive to malonyl-CoA and etomoxir. These results indicate that the histidine residues His-131 and His-340 are the sites responsible for the interaction of these two inhibitors, which inhibit COT by interacting with the same sites.